The Influence of Education, Training and Teaching Experience on the Professionalism of Public Primary School Teachers in Segeri Sub-District, Pangkep District - Asriani, Asriani; Rahmawati, Rahmawati; Sulfaidah, Sulfaidah; W, Muhammad Fahreza (CV. Rayyan Dwi Bharata, 2025)
The objectives of this study are: (1) To explain the effect of education level on teacher professionalism. (2) To explain the effect of training on teacher professionalism. (3) To explain the effect of teaching experience on teacher professionalism. (4) To explain the effect of education, training and teaching experience on teacher professionalism in SDN Wilayah I, Segeri District, Pangkep Regency. Data collection used questionnaires, documentation, observation and interviews. The results of the research conducted show that (1) the level of education has a negative and significant effect on teacher professionalism in SDN Wilayah I, Segeri Subdistrict, Pangkep Regency. (2) There is a significant positive effect of training on teacher professionalism in SDN Wilayah I, Segeri Subdistrict, Pangkep Regency. (3) There is a significant positive influence between prosecution experience on teacher professionalism in SDN Wilayah I, Segeri Subdistrict, Pangkep Regency. (4) There is a simultaneous positive and significant influence between the level of education, training and teaching experience on teacher professionalism in SDN Wilayah I, Segeri Subdistrict, Pangkep Regency.